Women’s preferences for cancer risk management strategies in Lynch syndrome - Sun, Charlotte C. (Gynecol Oncol, 2019)
OBJECTIVE: We assessed preferences for cancer risk management strategies for Lynch syndrome (LS) in LS-affected women. METHODS: Women with LS aged ≥ 25 years evaluated 9 cancer risk management strategies using a visual analog scale (VAS) and modified standard gamble (SG). For the VAS, women ranked each strategy ranging from 0 (least preferred) to 100 (most preferred). VAS scores were calculated by dividing the corresponding number by 100. Scores closer to 1.0 reflected more favorable strategies. For the SG, participants were asked to specify their expected threshold of lifetime risk of endometrial or colorectal cancer, ranging from 0 to 100%, at which they would consider undertaking each strategy. Strategies included chemoprevention, cancer screening, and preventive surgery. Cancer worry and perceived cancer risk measures were collected on a subset of participants. RESULTS: Sixty-one women completed preference assessments. By VAS, annual combined screening was the most preferred, followed by annual screenings and chemoprevention with oral contraceptives. By SG, women were the most willing to endorse oral contraceptives and biannual screening strategies at the lowest threshold of lifetime risk followed by annual screening strategies. Surgical interventions were the least preferred strategies using both VAS and SG. Women with a family history of gynecologic or colorectal cancer were less likely to consider prevention or screening options compared to women without a family history. Cancer worry was higher among women with a positive family history of LS cancer. CONCLUSION: Understanding women’s preferences may facilitate optimal use and adherence to cancer risk management strategies.